Valence determinations and oxybarometry on FIB‐sectioned olivine and pyroxene using correlated Ti, V, and Cr micro‐XAFS spectroscopy: Evaluation of ion‐milling effects and application to Antarctic micrometeorite grains. (15th December 2020) - Sutton, S. R.; Brearley, A. J.; DobricĂ, E.; Lanzirotti, A.; Newville, M.; Tschauner, O.
Abstract: X‐ray absorption fine structure (XAFS) spectroscopy methods have been applied to focused ion beam (FIB) produced sections of olivine and pyroxene for determining the valence states of Ti, V, and Cr and inferring oxygen fugacities of formation for each element. High‐quality XAFS spectra were obtained for all three elements for analytical voxels of ~10 pg and usable spectra down to the pg level are achievable. The extraterrestrial samples studied here were olivine and pyroxene from chondrules in Semarkona (LL3.00), olivine from chondrules in Kainsaz (CO3.2), and an olivine and a pyroxene grain from two Antarctic micrometeorites (AMM). The general agreement between calculated thin section and FIB section valences strongly suggests that there is negligible alteration of Ti, V, and Cr valences during FIB sectioning. The inferred oxygen fugacities for the AMM olivine support an equilibrium igneous history similar to results seen for some achondrites. For the pyroxene, highly reduced Cr, coupled with relatively oxidized Ti, suggests an origin in a mildly metamorphosed chondritic parent body. These results demonstrate that this FIB and micro‐XAFS approach is promising for establishing the oxidation states of minute monomineralic grains of diverse extraterrestrial origins, including materials from sample‐return spacecraft, such as the Stardust, OSIRIS‐REx, Hayabusa, and Hayabusa2 missions.